The elderly's satisfaction with physical activity programs in senior welfare centers - Yang-Hun Jung; Jeong-Beom Park; Austin Kang; Kuy-Chung Cho (Frontiers Media S.A., 2023)
IntroductionHealthcare for the aging population has become a crucial issue in South Korea to maintain the elderly's quality of life, and physical activity is of primary importance for older adults. This study evaluated the exercise characteristics and satisfaction of the elderly who participated in physical activity programs provided by senior welfare centers in South Korea.MethodsWe surveyed 266 participants to learn the characteristics of the elderly's exercise participation and their satisfaction with instructors, exercise programs, and facilities provided by senior welfare centers. A total of 263 copies were analyzed using the SPSS 23.0 statistical software.Results and discussionThe top three physical activity programs that the elderly participated in senior welfare centers were dancing (25.3%), gymnastics (24.8%), and table tennis/badminton (13.2%). There were significant differences in respondents' satisfaction according to sex, education level, spouse, family type, and monthly income per household (p < 0.05). The elderly were satisfied with programs (4.183 ± 0.483), facilities (3.881 ± 0.483), and instructors (3.604 ± 0.483) in order. Also, this study shows that user satisfaction differs depending on the demographic characteristics (gender, education, marital status, family type, economic status) and the characteristics of the exercise participation of the elderly (exercise duration, participation period).ConclusionsIn conclusion, we presented the elderly's satisfaction with physical activity programs in senior welfare centers, suggesting that the elderly need physical activity programs according to their demographic and exercise characteristics.